Effectiveness of Divorce Settlement Through a Circuit Court at the Bangko Religious Court - Desmarita Desmarita (Dinasti International Journal of Education Management And Social Science, 2022)
Desmarita MHK. 1622619 "Effectiveness of Divorce Settlement Through a Circuit Court at the Bangko Religious Court". The Bangko Religious Court has carried out in the form of circuit court activities from 2012 until now. The purpose of carrying out this circuit court is to provide an convenience in service so that all matters are easy and light for the community in order to seek legal protection and justice to realize a simple, fast, precise and cost-free judicial process. As well as increasing legal awareness for the community, and making it easier for people who have divorce cases that occur in some remote and difficult to reach areas in a short time. With the implementation of this Circuit Court system, the public can take advantage of this Circuit Court, in order to speed up and facilitate and save costs during the litigation process. While the main problems in this study are (1) How is the implementation of the settlement of divorce cases through a mobile court conducted by the Bangko Religious Court, (2) What are the factors that are always an obstacle and supporter in the divorce case settlement process mobile trial at the Bangko Religious Court, (3) How is the solution to the implementation of the mobile court in the settlement of divorce cases to the development of the divorce rate that occurred at the Bangko Religious Court. The research approach method used in the process and implementation of this research is an "empirical descriptive" approach, which describes problems based on the results of research in the field. From this research, the writer concludes that: (1) The implementation of the Circular Session has been running effectively and has had a very positive impact on the poor or the lower middle class (justice for the poor). Judging from the close distance between the places where the round-trip meeting is being carried out, the place where the parties involved are staying, which makes the transportation costs for the parties involved more expensive and can save time. If the case has not been completed while the funds have run out, the next trial will be held at the Bangko Religious Court. While the supporting factors are very numerous, one of which is the cohesiveness of the judges and the support from where the circuit court is held. (3) Conducting socialization to the community regarding the importance of legal certainty in marriage and divorce because it has a very large impact on the community regarding parties in marriage and child status, as well as conducting circuit courts in more remote districts. The mobile court in the settlement of divorce cases at the Bangko Religious Court does not have any implications for the increase in the divorce rate at the Bangko Religious Court as seen from the ups and downs of divorce cases resolved through circuit courts.